2012
DOI: 10.1016/j.cell.2012.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Epithelial Tumors and Field Cancerization from Loss of Mesenchymal CSL Signaling

Abstract: Summary It is currently unclear whether tissue changes surrounding multifocal epithelial tumors are a cause or consequence of cancer. Here, we provide evidence that loss of mesenchymal Notch/CSL signaling causes tissue alterations, including stromal atrophy and inflammation, which precede and are potent triggers for epithelial tumors. Mice carrying a mesenchymal-specific deletion of CSL/RBP-Jκ, a key Notch effector, exhibit spontaneous multifocal keratinocyte tumors that develop after dermal atrophy and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
196
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(209 citation statements)
references
References 33 publications
6
196
1
6
Order By: Relevance
“…Other recent studies provide further evidence supporting our finding that stromalderived growth factors and FGF7 in particular contribute to SCC pathogenesis. Deregulated signaling in stroma cells within the dermis induces a field cancerization effect associated with increased secretion of growth factors including FGF7 from the stroma (59), and transgenic expression of FGF7 itself results in transformation of the epithelium (60,61). We have also found that other FGFR2 ligands, including FGF1 and FGF10, are elevated in the tumor microenvironment, suggesting that multiple ligands could potentially contribute to tumor progression.…”
Section: Discussionmentioning
confidence: 62%
“…Other recent studies provide further evidence supporting our finding that stromalderived growth factors and FGF7 in particular contribute to SCC pathogenesis. Deregulated signaling in stroma cells within the dermis induces a field cancerization effect associated with increased secretion of growth factors including FGF7 from the stroma (59), and transgenic expression of FGF7 itself results in transformation of the epithelium (60,61). We have also found that other FGFR2 ligands, including FGF1 and FGF10, are elevated in the tumor microenvironment, suggesting that multiple ligands could potentially contribute to tumor progression.…”
Section: Discussionmentioning
confidence: 62%
“…Molecular evidence to support this notion followed in the late 1990s primarily concentrating on TP53 mutation (Franklin, Gazdar et al 1997) but also describing unique epigenetic phenomena (Suzuki, Watkins et al 2004). In the skin, field cancerisation characterised by TP53 mutation has been well described (Jonason, Kunala et al 1996;Stahl, Stranneheim et al 2011) and recent data now show that field change can be induced in mice through inhibition of Notch signaling within the stroma rapidly promoting spontaneous cSCC (Hu, Castillo et al 2012). We have shown NOTCH1 mutation arising in normal and tumor tissue in close proximity suggesting that such a mechanism may be active in human skin (South, Purdie et al 2014).…”
Section: Field Change In Sccmentioning
confidence: 86%
“…Arguably the most abundant cell type in the TME, CAFs can be distinguished from other, normal fibroblasts thru their increased rate of proliferation and differential expression of extracellular matrix (ECM) components (Bhowmick, Neilson et al 2004;Kalluri and Zeisberg 2006;. It has been suggested at least in HNSCC, that resident and bone marrow (BM)-derived mesenchymal stem cells (MSCs) are actually precursors of the stroma and contribute to blood-and lymph angiogenesis, as well as produce tumor-associated (Hu, Castillo et al 2012) myofibroblasts (De Boeck, Narine et al 2010). Markers traditionally used to identify CAFs have been smooth muscle actin, vimentin and PDGFR but significant heterogeneity can be observed even in murine models of cancer suggesting that one marker alone will not identify all CAF in the TME (Sugimoto, Mundel et al 2006).…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…In addition, dermal atrophy accompanied by chronic stromal inflammation, caused by mesenchyme-dependent inhibition of Notch signaling, was found to be a driver for multifocal SCC development. 21 In fact, chronic inflammation promoted by immune cells was recently recognized as one of the cancer hallmarks. 22 Increased inflammation can occur in a variety of normalaged tissues, a phenomenon dubbed inflammaging.…”
mentioning
confidence: 99%